Intratumoral pan-ErbB targeted CAR-T for head and neck squamous cell carcinoma: interim analysis of the T4 immunotherapy study - Papa, Sophie; Adami, Antonella; Metoudi, Michael; Beatson, Richard; George, Molly Sarah; Achkova, Daniela; Williams, Evangelia; Arif, Sefina; Reid, Fiona; Elstad, Maria; Beckley-Hoelscher, Nicholas; Douri, Abdel; et al. (Journal for immunotherapy of cancer, 2023)
BackgroundLocally advanced/recurrent head and neck squamous cell carcinoma (HNSCC) is associated with significant morbidity and mortality. To target upregulated ErbB dimer expression in this cancer, we developed an autologous CD28-based chimeric antigen receptor T-cell (CAR-T) approach named T4 immunotherapy. Patient-derived T-cells are engineered by retroviral transduction to coexpress a panErbB-specific CAR called T1E28ζ and an IL-4-responsive chimeric cytokine receptor, 4αβ, which allows IL-4-mediated enrichment of transduced cells during manufacture. These cells elicit preclinical antitumor activity against HNSCC and other carcinomas. In this trial, we used intratumoral delivery to mitigate significant clinical risk of on-target off-tumor toxicity owing to low-level ErbB expression in healthy tissues.MethodsWe undertook a phase 1 dose-escalation 3+3 trial of intratumoral T4 immunotherapy in HNSCC (NCT01818323). CAR T-cell batches were manufactured from 40 to 130 mL of whole blood using a 2-week semiclosed process. A single CAR T-cell treatment, formulated as a fresh product in 1–4 mL of medium, was injected into one or more target lesions. Dose of CAR T-cells was escalated in 5 cohorts from 1×107−1×109 T4+ T-cells, administered without prior lymphodepletion.ResultsDespite baseline lymphopenia in most enrolled subjects, the target cell dose was successfully manufactured in all cases, yielding up to 7.5 billion T-cells (67.5±11.8% transduced), without any batch failures. Treatment-related adverse events were all grade 2 or less, with no dose-limiting toxicities (Common Terminology Criteria for Adverse Events V.4.0). Frequent treatment-related adverse events were tumor swelling, pain, pyrexias, chills, and fatigue. There was no evidence of leakage of T4+ T-cells into the circulation following intratumoral delivery, and injection of radiolabeled cells demonstrated intratumoral persistence. Despite rapid progression at trial entry, stabilization of disease (Response Evaluation Criteria in Solid Tumors V.1.1) was observed in 9 of 15 subjects (60%) at 6 weeks post-CAR T-cell administration. Subsequent treatment with pembrolizumab and T-VEC oncolytic virus achieved a rapid complete clinical response in one subject, which was durable for over 3 years. Median overall survival was greater than for historical controls. Disease stabilization was associated with the administration of an immunophenotypically fitter, less exhausted, T4 CAR T-cell product.ConclusionsThese data demonstrate the safe intratumoral administration of T4 immunotherapy in advanced HNSCC.